IMPLEMENTASI PERMENRISTEKDIKTI NOMOR 55 TAHUN 2018 DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS WIJAYAKUSUMA PURWOKERTO - Ma'muri, Johar (Majalah Ilmiah Dinamika Administrasi (MIDA), 2024)
The implementation of Permenristekdikti No. 55 of 2018 at the Faculty of Social and Political Sciences, Wijayakusuma University, Purwokerto will depend on how university and faculty leaders manage policies. Policy implementation is centralized and starts from central level actors, and decisions are taken from the central level. In this research, researchers used descriptive methods. According to Nazir (1988:63) the descriptive method is a method used to examine the status of a group of people, an object, condition, system of thought or a class of events in the present. With 2 aspects assessed in policy implementation, namely; (1) Compliance and (2) What's Happening and Why?. Caring for the nation's ideology is the responsibility of all people involved in campus life, especially within the Faculty of Social and Political Sciences, Wijayakusuma University, Purwokerto. Therefore, it is necessary to implement Permenristekdikti number 55 of 2018 concerning the development of Pancasila ideology in student activities in higher education. And establishing an organization that focuses on safeguarding the Pancasila ideology as the nation's identity.